P267 Fronto-executive cognitive functioning predicts antidepressant response to transcranial direct current stimulation. Issue 3 (March 2017) - Martin, D.; Yeung, K.; Loo, C.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) is a promising new treatment for depression, however, clinical trials to-date indicate variable efficacy, thereby raising the need to identify inter-individual predictors of response. Objective: In the current study we aimed to investigate pre-treatment neurocognitive performance as a predictor of antidepressant response to tDCS. Materials and methods: Data was pooled from five clinical trials, including two randomised controlled trials (RCTs), which investigated the antidepressant effects of anodal tDCS (1–2 mA) administered to the prefrontal cortex for 20 min over a course of between 10 and 20 sessions. Data from 71 cases was included in the analysis. Mood was assessed before and after an acute course of treatment using the Montgomery-Åsberg Depression Rating Scale. The following neurocognitive tests were administered prior to treatment: Simple and choice reaction time, the Symbol Digit Modalities Test (SDMT), Rey Auditory Verbal Memory Task (RAVLT), Digit Span, and the Controlled Oral Word Association Test (COWAT). Results: Better pre-treatment fronto-executive functioning, as indicated by SDMT and COWAT performance, predicted antidepressant response to tDCS after controlling for confounds. A cognitive composite which comprised from both SDMT and COWAT performance independently predicted better antidepressant response in an adjusted model ( β  = −.35, p  = .001). Higher depressive severity at pre-treatment was a negative predictor of antidepressant response ( β  = .36, p  = .001). Conclusions: Pre-treatment fronto-executive functioning on measures subserved by the left prefrontal cortex, the site of stimulation, is a predictor of response for tDCS treatment for depression. This study highlights the importance of inter-individual neurobiological differences in mediating tDCS antidepressant effects.